PENGARUH SIKAP REMAJA TENTANG PERILAKU SEKS DAN NIAT REMAJA DALAM MELAKUKAN PERILAKU SEKS BERESIKO - Wahyu Tri Ningsih; Hadi Purwanto; Titik Sumiatin (Universitas Muhammadiyah Jember, 2017)
Adolescents have high curiosity, including the issue of sexuality. Adolescent curiosity about sexuality due to the development phase of teenagers who enter puberty characterized by the maturation of the reproductive system and the production of sex hormones. This study aims to determine the influence of attitudes about seks behaviortoward adolescent intention of doing risky sexual behavior. This study used analytic design with cross sectional approach. The sample in this study were high school students in the districts of Tuban amounted to 349 people by using simple random sampling. The data collection done by using the a questionnaire. The statistical test used is ordinal logistic regression to examine the influence between variables. The result showed that there was influence adolescent attitudes toward intention in sexual behavior (p = 0.000). If the adolescent attitude positive, the teen has no intention of doing risky sexual behavior. Adolescents can maintain and improve the knowledge and a positive attitude by the way can sort and filter the information gathered from the mass media about sexual behavior